Tangential role of therapeutics in COVID-19 induced Mucormycosis: A Review - Dr. Pooja Raj; Dr. Kirti.R. Bhati (East Asian Journal of Multidisciplinary Research, 2022)
Due to restricted treatment alternatives that were excessively expensive, people resorted to an integrated strategy with other relevant professions to reduce the burden on a single therapy. Objective: To estimate our ability to live with the limited disease load while reviewing the likely influence of holistic science on sustaining health dimensions. Method: PubMed, Google Scholar, and other embedded websites chose 205 Mucormycosis papers for examination, and 69 publications were chosen from diverse sources for the study. The study concentrated on clinical symptoms, risk factors for mortality, and future integrative therapeutic options, with a particular emphasis on Indian demographic data. Data were extracted from the study about India and Indian peoples based on descriptions and facts. Conclusion: Integrative preventive strategies and therapeutic approaches can reduce the burden on one drug and can prove cost-effective with better.